An Analysis of Federal and Municipal Chatbots in Germany - Traubinger, Verena (2024)
Chatbots are often encountered in e-commerce and specifically customer service. In the last years, governmental institutions are also using them more often as a communication channel for citizens. In this paper we report our findings on the landscape of publicly available chatbots in federal states and large city municipalities in Germany. We collected a dataset of 25 chatbots and analysed them with a codebook of 12 feature characteristics and 12 chatbot interaction patterns. These patterns describe how interactive elements are used in a chatbot conversation to guide the user. Our results show the presented features of the assessed municipal chatbots in terms of avatars, names, and layout. We also discuss our findings concerning the use of existing chatbot interaction patterns, and introduce four new patterns based on this real-world analysis. Our analysis also focuses on the differences between governmental and e-commerce chatbots in terms of their implementation of features and interaction patterns.